Creación literaria en el marco de la enseñanza de la física con estudiantes de grado octavo de bachillerato - Carvajal Córdoba, Fabián Ricardo (Revista Científica, 2011)
The teaching of Physics must be related with other subjects. Therefore, the teacher's performance should lead the knowledge of Physics from other perspectives, such as reading, writing and creative thinking. According to this, it has been proposed to establish the relationship between Creative Writing and Physics through an exercise with Eighth Grade students following the basic postulates of the Writing Across Curriculum movement.